Synthesis and Characterization of the Hexafluoridomolybdates(V) A[MoF6] (A = Li – Cs). Issue 19 (6th May 2020) - Stene, Riane E.; Scheibe, Benjamin; Petry, Winfried; Kraus, Florian
Abstract: Invited for the cover of this issue is the group of Florian Kraus from Philipps‐Universität Marburg, Germany. The cover image shows a typical fluorine chemist synthesizing lithium hexafluoridomolybdate(V), Li[MoF6 ]. Abstract : Such "dry" separation techniques will lead to significant reductions in nuclear waste … Read more about the story behind the cover in the Cover Profile and about the research itself in the Full Paper by F. Kraus et al.